Green Patenting Efficiency of Higher Educational Institutions in India (Journal of Intellectual Property Rights (JIPR), 2024)
Considering the present state of the global environment, it is imperative for academic institutions to prioritise the promotion of sustainability. The potential challenges faced by rapidly developing economies such as India can be addressed through the implementation of innovative and science-driven approaches such as the creation of green technologies. The present investigation aimed to analyse the prevailing patterns of environmentally sustainable technologies. To evaluate the efficiency of the leading 50 higher educational institutions according to NIRF 2022, this study employed data envelopment analysis. The results indicate that 16 universities have made noteworthy advancements in the creation of technologies that foster environmental sustainability. Furthermore, leading academic institutions collectively filed 1217 patents.